IMPLEMENTASI KURIKULUM PENDIDIKAN PRANIKAH DI KANTOR URUSAN AGAMA (KUA) KECAMATAN CIPUTAT KOTA TANGERANG SELATAN - Marhamah Saleh Saleh; Neng Yunita Yulia (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
This study aims to determime the pre-marital education curriculum used by the office of Religious Affairs of Ciputat Sub-District, South Tangerang City and describe the learning process of pre-marital education, as well as describe inhibiting factors in the implementation of pre-marital education. The method used is descriptive qualitative, this research uses a case study approach that only focuses on one phenomenon.Data collection techniques by conducting observations, interviews and documentation. The analysis uses is data reduction, presenting the data, the drawing conclusions. In this study, the respondents were extention workers from the Office of Religious Affairs (KUA). Thus study concludes that the curriculum used in KUA, Ciputat Sub-District South Tagerang City is the curriculum contained in the regulation of the DirectorGeneral of Islamic Community Guidence No. DJ/II/542 of 2013 concernig guidelines for the implementation of pre-marriage Guidence Module prepared by the Directorate of KUA and Family Sakinah, the Directorate General of Islamic Community Guidance, Ministry of Religion of Republic of Indonesia. The module contains debriefing materials of families and various solutions to problems in the family. While the learning process in pre-marital educations is prepared by being given a special module for prospective brides with the title Sakinah Family Development, Directorate General of Islamic Community Guidance. Ministry of Religion, RI with 16 hours of lessons per week. The obstacles in pre-merital education contained in internal factors, namely insfrastructure. While the external factor in pre-merital education is the lack of public awereness in attending pre-marital education.